Use of Mitomycin C to Distinguish Brucella abortus Field Strains from the Vaccinal Brucella abortus Strain 19 - Myers, Donald M. (1969)
Field strains of Brucella abortus were resistant to mitomycin C, whereas strain 19 was sensitive; therefore, the antibiotic was used to distinguish B. abortus strain 19 from other strains.